The Outcome of Voice in Endoscope Assisted Intra-Operative Identification of External Branch of Superior Laryngeal Nerve during Thyroid Surgery - Dr.Easter Suchen; Dr.Kripamoy Nath (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: The external branch of the superior laryngeal nerve (EBSLN) innervates the cricothyroid muscle (CTM),to promote lengthening and thinning of the vocal fold. The EBSLN is at an increased risk during superior thyroid pole ligation during thyroidectomy which can result in significant post operative complications in voice production. This injury can be avoided by intraoperative identification of the nerve which can be aided by endoscope assisted magnification during thyroid surgery. Aims: (I) To identify the External Branch of Superior Laryngeal Nerve (EBSLN), along with Recurrent Laryngeal Nerve (RLN), during thyroid surgery by adopting endoscopic magnification along with routine dissection methods. (II) To determine the significance of intra-operative identification of EBSLN for preservation of quality of voice following Thyroid surgery. Methodology: A prospective institutional comparative study was carried out for 2 years from November, 2022 to November, 2024 with a sample size of 80 patients. The sample size was divided into two equal groups of 40 patients each. In Group A, Thyroid surgery was conducted by employing conventional dissection techniques. In Group B, special care was taken to preserve the EBSLN with the aid of endoscopic magnification. The patients were clinically evaluated for any changes in voice, particularly related to injury to the EBSLN; by assessing for hoarseness of voice, easy fatigability, inability/difficulty to produce high pitched voice; at day 3 and one month following surgery. Furthermore, patients underwent indirect and flexible videolaryngoscopy and voice recording and the results were statistically evaluated. Results: Use of endoscopic magnification along with routine dissection techniques, helped in the preservation of EBSLN in Group B patients. Cernea Type 1 variation of EBSLN was the most common (74%). The voice outcome assessment in Group B patients was found to be superior to that in Group A. Conclusion: The preservation of EBSLN along with RLN during thyroid surgery plays a major role, for conserving a superior quality of voice and it has been found that endoscopic magnification aids in identification of EBSLN and its variants.